La nidificación de la Harpía (Harpia harpyja) en Argentina - Chebez, Juan Carlos; Silva Croome, Marcelo; Serret, Alejandro; Taborda, Alejandro (El Hornero, 1990)
Este artículo no cuenta con un resumen.